Biennial review of health care management - Blair, John D.; Fottler, Myron D.; Savage, Grant T. 1954- (Advances in health care management ;, 2011)
This is the second biennial volume reviewing the state-of-the-art on a wide variety of micro and macro health care management topics in the popular "Advances in Health Care Management" series. It proudly showcases reviews of both empirical and conceptual research in specific areas of health care management, including topics in three basic areas: reviews of empirical and conceptual research on health care industry-specific topics, e.g., role of physicians; reviews of empirical and conceptual research on different types of health care organizations focusing on issues specific to such organizations or their segments of the health care industry, e.g., hospitals, managed care organizations; and, reviews of empirical and conceptual research on health care organizations focusing on topics or variables which cover various sub-disciplines of management, e.g., organizational change or entrepreneurial opportunity recognition. New and established scholars discuss such topics within their expert area of research, as well as emerging themes and divergent views, giving their unique perspective on the directions that will help build theory and improve the practice of health care management.